Factores socioeconómicos que influyen en la probabilidad de desarrollar actividades de comercio ambulatorio en Iquitos año 2022 - Fachin Rengifo, Angela Patricia (2025)
Street trading is an economic activity that takes place in public spaces, such as streets, squares, markets, piers, among others. It presents itself as an opportunity to earn income in contexts of poverty and unemployment. In this sense, this research analyzes the influence of socioeconomic factors on the probability of developing street trading activities in the city of Iquitos during the year 2022. For the development of the research, a quantitative approach was chosen, at an correlational level and a non-experimental cross-sectional design, with a population defined by 197,132 independent workers in the city of Iquitos in 2022. The results reveal that 26.32% of independent workers in Iquitos are engaged in street trading. Based on them, it is established that the type of residence, the level of poverty and financial inclusion are factors that influence the probability of developing street trading activities. Otherwise, sex and educational level are not factors that influence the probability of developing street trading activities in the city of Iquitos during the year 2022.